Motor Coordination in Children: A Comparison between Children Engaged in Multisport Activities and Swimming - Dušan Stanković; Maja Horvatin; Jadranka Vlašić; Damir Pekas; Nebojša Trajković (MDPI AG, 2023)
Motor coordination has a crucial role in various physical activities and sports, highlighting its significance in overall movement proficiency and performance. This study aimed to compare motor coordination in children engaged in multisport versus swimming activities. The participants of this study included 180 boys and girls (girls = 87) aged 8.25 years ± 0.89. A total of three groups were included: group 1 consisted of inactive children, group 2 included children participating in swimming, and group 3 included children enrolled in multisport. Motor coordination was assessed using the Kiphard-Schilling body coordination test, evaluated by motor quotient (MQ): walking backwards, hopping for height, jumping sideways, and moving sideways. Additionally, a total motor quotient (Total MQ) was calculated based on the performance in all four tests. ANOVA revealed a significant difference in Total MQ and all subtests between the groups (p < 0.01). A significant difference in Total MQ was found not only between the inactive and multisport groups (Diff = 19.8000; 95%CI = 13.1848 to 26.4152; p = 0.001) but also between the multisport and swimming groups (Diff = 12.8000; 95%CI = 6.3456 to 19.2544; p = 0.001). In conclusion, the results revealed that children involved in multisport activities exhibited significantly better motor coordination compared to both the swimming group and the inactive group. Therefore, to enhance the growth of motor coordination abilities, it is crucial that parents, instructors, and coaches encourage kids to engage in multisport physical activities on a daily basis.